Economic effects of IFRS adoption in Brazil: An empirical analysis of stock price synchronicity - Santana, V.; Sarquis, R.; Lourenço, I.; Salotti, B.; Múrcia, M. (2014 American Accounting Association's Annual Meeting, 2014)
This study aims to identify the impact of IFRS adoption in stock price synchronicity of Brazilian capital market through its influence on how much and in which way firm-specific information is incorporated by stock prices. There are divergences in the literature about how IFRS adoption (specially the mandatory adoption) affects synchronicity in countries with poorer institutions. Our results indicate that IFRS adoption in Brazil has reduced stock price synchronicity and, consequently, increased the efficiency of resource allocation and potential portfolio diversification. These findings support the view that IFRS adoption facilitates firm-specific information flows into the market, improving the informational environment. This findings show that investment conditions in Brazil have improved, opening better opportunities for foreign investments on the country, contributing to financial globalization and market integration.